Efektivitas Penggunaan Hidrogel Kratom Terhadap Kadar Gula Darah Pada Ulkus Diabetikum - Rihhadatulays, Khuzaimah Nur Juhanifah; Pramesti, Rosandhy Alifyah; Hanafi, Eka Satria Akbar Ferdinan; Jazuli, Muhammad Aqil Siroj; Salim, Hotimah Masdan; Amani, Fariska Zata; Aisyah, Aisyah (Universitas Ciputra Surabaya, 2025)
Type 2 diabetes mellitus is a chronic metabolic disorder characterized by hyperglycemia resulting from insulin resistance and pancreatic β-cell dysfunction. One of the most common complications is diabetic ulcers, which are often associated with vascular impairment, infection, and poor glucose stability. The search for alternative therapies continues to develop, including the use of Mitragyna speciosa (kratom) leaves, which contain mitragynine and flavonoids that have been shown to inhibit α-glucosidase and enhance antioxidant activity. This study aimed to evaluate the effect of kratom hydrogel on blood glucose levels in an animal model of diabetic ulcers. Using a posttest-only control group design, mice (Mus musculus) were induced with streptozotocin to establish a type 2 diabetes model. The animals were divided into three groups: positive control, 5% kratom hydrogel, and 15% kratom hydrogel. Blood glucose levels were measured weekly over a two-week period. Data were analyzed using the Kruskal–Wallis test followed by Dunn’s multiple comparison test. The results showed differences in blood glucose levels among all treatment groups. The 15% kratom hydrogel group demonstrated a significant reduction in blood glucose, approaching near-normal levels compared with the positive control (p < 0.05). Statistical analysis indicated a more dominant effect compared to the variation of treatment types. These findings suggest a synergistic mechanism through α-glucosidase inhibition and enhanced antioxidant activity. Therefore, kratom hydrogel has potential as a complementary therapy for glycemic control in patients with type 2 diabetes mellitus complicated by diabetic ulcers.